The Efficacy of Special School Teachers in Teaching Sexual Violence Prevention in Terms Of Gender, Training Experience And Length of Teaching - Sholihah, Warotsatus; Mahanani, Fatma Kusuma; Mukhlis, Hamid (UK Institute, 2022)
Children who have special needs have a greater potential to experience sexual violence than normal children. The teacher is the party who is also responsible for protecting children with special needs from sexual violence. High efficacy is needed in teaching sexual violence prevention to Children with special needs considering their physical and mental limitations. There are different results regarding the results of efficacy training in teaching children with special needs prevention, therefore it is necessary to investigate what factors are related. The factors used in this study are gender, training experience and length of teacher teaching. Therefore, this objective of the study was to find differences in the efficacy of special education teachers in teaching children with special needs prevention in terms of gender, training experience and length of teaching. The method used is quantitative comparison. Subjects consisted of 51 male teachers and 76 female teachers. The sampling technique used is cluster random sampling. The data were taken using the efficacy scale of special school teachers in teaching prevention of sexual violence which consisted of 35 valid items with a significance level between 0.50-1.00 and reliability of 0.960, and the discrepancy between items ranging from 0.453 to 0.885. The analytical method used is the Mann Whitney U-Test and Kruskal Wallis test. The results of data processing showed a significance value of 0.148 for gender, 0.907 for training experience and 0.554 for the length of teaching. Because all three are less than 0.05, the hypothesis which states â€œthere is a difference in the efficacy of special school teachers in preventing sexual violence in terms of gender, training experience and length of teachingâ€ is rejected.